Efficacy of typhoid conjugate vaccine in Nepal: final results of a phase 3, randomised, controlled trial. Issue 11 (November 2021) - Shakya, Mila; Voysey, Merryn; Theiss-Nyland, Katherine; Colin-Jones, Rachel; Pant, Dikshya; Adhikari, Anup; Tonks, Susan; Mujadidi, Yama F; O'Reilly, Peter; Mazur, Olga; Kelly, Sarah; Liu, Xinxue; et al.
Summary: Background: Typhoid fever is a major public health problem in low-resource settings. Vaccination can help curb the disease and might reduce transmission. We have previously reported an interim analysis of the efficacy of typhoid conjugate vaccine (TCV) in Nepali children. Here we report the final results after 2 years of follow-up. Methods: We did a participant-masked and observer-masked individually randomised trial in Lalitpur, Nepal, in which 20 019 children aged 9 months to younger than 16 years were randomly assigned in a 1:1 ratio to receive a single dose of TCV (Typbar TCV, Bharat Biotech International, India) or capsular group A meningococcal conjugate vaccine (MenA). Participants were followed up until April 9, 2020. The primary outcome was blood culture-confirmed typhoid fever. Cases were captured via passive surveillance and active telephone surveillance followed by medical record review. The trial is registered at ISRCTN registry, ISRCTN43385161 and is ongoing. Findings: From Nov 20, 2017, to April 9, 2018, of 20 119 children screened, 20 019 participants were randomly assigned to receive TCV or MenA vaccine. There were 75 cases of blood culture-confirmed typhoid fever included in the analysis (13 in the TCV group and 62 in the MenA group) over the 2-year period. The protective efficacy of TCV against blood culture-confirmed typhoid fever at 2 years was 79·0% (95% CI 61·9–88·5; p<0·0001). The incidence of typhoid fever was 72 (95% CI 38–123) cases per 100 000 person-years in the TCV group and 342 (95% CI 262–438) cases per 100 000 person-years in the MenA group. Adverse events occurring within the first 7 days post-vaccination were reported previously. Interpretation: The final results of this randomised, controlled trial are in keeping with the results of our published interim analysis. There is no evidence of waning protection over a 2-year period. These findings add further support for the WHO recommendations on control of enteric fever. Funding: Bill & Melinda Gates Foundation.